The Potential of Peripheral Neighborhoods for the Development of Urban Green in Latin American Cities, the Case of Algeria, Quito, Ecuador - Moya S.; Muñoz D.; Ortiz, F (My University, 2023)
This article proposes an analysis of the policies and strategies of the city of Quito for the development of urban green, for which the climate action plan of Quito and the plans to be fulfilled until 2030 have been reviewed, as well as the metropolitan corridor and its potential as a green corridor, after this the characteristics of the sector “La Argelia” have been analyzed. as an example of the characteristics of the peripheral neighborhoods of Quito, in order to show the potential that this type of environment has for the development of urban green, in this case from an urban agriculture approach, which could also provide these spaces not only with an economy, but with a circular metabolism, that contributes to the development of the neighborhood and the city. © 2023, The Author(s), under exclusive license to Springer Nature Switzerland AG.
Keywords: Berlin/Ambrosio; Ectasia Corneal; Edge-Sobel filter; Image processing; Keratoconus